Microstructure and Mechanical Properties of Modified Ductile Ni-resist With Higher Manganese Content - Mohd Rashidi, Maarof (Elsevier, 2013)
In this study, ductile Ni-resist with a minimum of 18 wt % nickel composition was modified. Up to 12 wt % manganese was added together with 10 wt % nickel to investigate the effects of the alloying elements on both its microstructure and mechanical properties. Compared to un-modified ductile Ni-resist, the results show a higher manganese composition on modifying ductile Ni-resist that increases carbide formation and hardness, and decreases tensile strength. However, the composition obtained was an austenitic iron matrix with a mixed result of graphite – shape nodularity. It appears that manganese plays a significant role in stabilizing the austenitic matrix phase as well as encouraging carbide formation.